ANALISA KESTABILAN MODEL MATEMATIKA UNTUK PENYEMBUHAN KANKER MENGGUNAKAN ONCOLYTIC VIROTHERAPY - Novellina, Via; Utomo, Robertus Heri Soelistyo; ., Widowati (MATEMATIKA, 2016)
Oncolytic virotherapy is one type of cancer treatment using oncolytic virus. In this paper, we will present a mathematical model for treatment of cancer using oncolytic virotherapy with the burst size of a virus (the number of new viruses released from lysis of an infected cell) and we considering the presence of syncytia which is a fusion between infected tumor cell and uninfected tumor cell. In this mathematical model we introduced the population of uninfected tumor cells which fusion in syncytia. So, in this model contains four population, which are, uninfected tumor cell population, infected tumor cell population, uninfected tumor cell population which fusion in syncytia, and free virus particles which are outside cells. Then, these models are analyzed to determine the stability of the equilibrium points. The stability of the equilibrium points criteria is based on basic reproduction number () and we show that there exist a disease free equilibrium point and a disease endemic equilibrium point. By the Routh-Hurwitz criterion of stability, we prove that the disease free equilibrium point is locally asymptotically stable if and the disease endemic equilibrium point is locally asymptotically stable if . In this numerical simulations using software Maple we have, if then the graphic of this mathematical model will reach the disease free equilibrium point, then virotherapy fails. While, if then the graphic of this mathematical model will reach the disease endemic equilibrium point, then virotherapy success.